Premium arrangement in the contemporary real estate transaction in Bauchi - Baba, Habu Mallam; Kasim, Rozilah; Usman Alhaji, Muktar; Ali Abdu, Abdullahi; Adam Muhammad, AbdulAzeez; Auwal, Umar (Science Arena Publications, 2018)
The premium arrangement in the real estate enables lessors to receive a lump sum of money and forfeit a part of rental income, while the lessee enjoys some profit rents. This transaction was not operational in the study area. This study investigated the position of the lessor on the awareness and practice of premium arrangement on the real estate transaction in Bauchi metropolis, using multiple regression and structural equation modelling with AMOS graphics. The analyses (both) multiple regression and structural equation modelling with AMOS revealed that the awareness and practice of premium arrangement in Bauchi metropolis have been a factor that can significantly influence the real estate transactions with corresponding benefits to both lessors and lessees in the study area. It was therefore recommended that the parties’ privy in the premium transaction to acknowledge the benefits to the lessor appeared to out-weigh the benefits to the lessee, thus the parties should be enjoined to comply with the existing rules and covenants of their lease